Thermal stability enhancement of mapbi3 film by incorporating poly(methyl methacrylate) additives and encapsulation layers for perovskite solar cell application - Chuo, Sing Ern (2023)
Perovskite solar cells (PSCs) are just like conventional solar cells with the exception of a perovskite material acting as its light absorbing layer, which converts solar energy to electrical energy. Due to the popularity of methylammonium lead iodide (MAPbI3) being used as a light-absorbing layer for PSCs, this study was conducted with the focus on PSCs containing MAPbI3. The successful deposition of metal oxide sol, which is low in cost, above the perovskite layer will lead to the commercialization of PSCs that utilizes metal oxides as its charge transport layers (CTL) which are both operationally stable and economic. In regards, post-annealing at around 150 ℃ is needed to deposit metal oxide sols above the perovskite layer. However, the weak thermal stability of MAPbI3 that lies underneath the metal oxide sol does not tolerate such heat and will thermally degrade, resulting in the loss of functionality of the device. In this work, PMMA was added as additives and as dual encapsulation layers to enhance the thermal stability of MAPbI3 films using vacuum-assisted solution processing (VASP) and antisolvent method. The results showed that 0.15 wt% of PMMA additives was the most prominent amount in enhancing the thermal stability of MAPbI3 films whereby a significant reduction in XRD peak intensity ratio of PbI2 to MAPbI3 was observed after 5 hours of thermal stressing. In this context, the peak intensity ratios of 8.6618 and 1.7577 were exhibited for pristine samples and 0.15 wt% PMMA-incorporated samples, respectively. Besides that, the peak intensity ratios of 1.0936 and 2.4087 were exhibited for dual and single-PMMA encapsulated samples, respectively. The lower peak intensity ratio of PbI2 to MAPbI3 signified lesser thermal degradation of MAPbI3 to PbI2. Apart from that, the lower formation of PbI2 needle grains and the retention of MAPbI3 UV-Vis band edge were observed for both 0.15 wt% PMMA-incorporated and dual PMMA-encapsulated samples. The thermal stability enhancement effects of both the incorporation of PMMA additives and dual PMMA encapsulation layers can be explained through the passivation of grain boundary defects at the film/air interface and within the MAPbI3 films. With this discovery, operationally stable and economic PSCs with higher thermal stability that allows the deposition of metal oxide sols as its CTLs may be developed.